Imperial careering and enslavement in the long eighteenth-century: the Bentinck family, 1710-1830s - Haggerty, Sheryllynne; Seymour, Susanne (Taylor & Francis, 2018)
This paper examines the claims of Eric Williams and the more recent Legacies of British Slave-Ownership projects regarding the influence of enslavement in the building of Britain and its empire through a multi-generational study of a leading British elite family, the Bentincks. Using the concept of imperial careering, it charts how four men from this family not typically identified as enslavers or abolitionists were entangled with enslavement in Britain’s Western and Eastern empires. It concludes that the influence of enslavement was extensive and mainly exploitative, but involved losses as well as gains for these elite protagonists.